AN INSTRUCTIONAL MODEL TO ENHANCE CONSCIOUS MIND AND SELF - REGULATION OF THE SIXTH GRADE STUDENTS BASED ON METACOGNITION, COLLABORATIVE LEARNING, AND SOCIAL COGNITIVE LEARNING THEORY - Tesprasit, Vorrapapha Tesprasit; Jantharajit, Nirat; Thongpanit, Phichittra (Academic Journal of Thailand National Sports University, 2024)
The research aims to 1) study the current state and need in learning management to strengthen the consciousness and self - regulation abilities of Sixth Grade students to support the development of the learning management model, 2) study the results of the out – for temporary learning management model to promote consciousness and self - regulation ability of learners, This research proceeded with studying the current state and needs to support the development of the instructional model, that was assigned the target groups for studying based on 4 schools under the Nakhon Phanom Municipality, through interviewing 4 related teachers, 12 students, and observing for 4 classes of learning activities to support the draft construct of the instructional model, and then assigned with quasi - experimental method to try - out the model draft with 37 students of research samples for sixth - grade level, in the Academic Year 2022, that obtained by cluster random sampling method. The research tools were composed of: 1) the interviewing forms for teachers and student’s information, and observing forms for class learning activities, 2) learning management plans, 3) the consciousness assessment form, and 4) the Self-regulation ability assessment form. The statistics used in this research study were mean, standard deviation and t - test for Dependent Samples. The research results found that: The target group of teachers needed to concentrate on student development for higher consciousness and self - regulation, based on curriculum goals and the schools needed. Whereas, some students expressed performance and communication with their peers in the context of the need to enhance valuable interaction and positive feelings through rationale support. Therefore, the researcher was interested in studying and developing a learning management model based on the knowledge of the metacognitive concepts, cooperative learning strategy, and social cognitive learning theory for improving consciousness and self-regulation of sixth - grade students, that instructional model was composed of 6 components and including 5 steps of learning activities, In addition, it revealed the result of expert judgment for appropriate learning management model with a high level of 4.10 (S.D. = 0.25). The result of the try - out instructional model with the sample group of students that assigned with related learning management had the post consciousness and self - regulation after learning higher than before learning at the level of significance .05.